Bilateral vestibulopathy affects spatial and temporal perception - Olga Kuldavletova; Deborah Cecilia Navarro Morales; Timothy R. Macaulay; Scott J. Wood; Michel Toupet; Charlotte Hautefort; Christian Van Nechel; Anthony Rengel; Adéla Kola; Thomas Fréret; Gaëlle Quarck; Pierre Denise; et al. (PLoS ONE, 2025)
This study assessed impairments in spatial and temporal perception in individuals with bilateral vestibulopathy (BVP). A total of 30 BVP subjects and 35 healthy controls (CTL) participated in a series of tests to assess their perception of distance (1–6 meters), angle (90–360 degrees), duration (2–10 seconds), and a combination of distance and angle during a triangle completion task (TCT). When performing distance and angle perception tasks separately, the BVP subjects showed larger errors than the CTL subjects. During the TCT, the BVP subjects walked longer paths and exhibited greater angle deviations compared to the CTL subjects. The angle deviations of the BVP subjects during the TCT were larger than when the angle perception task was performed separately. Moreover, the BVP subjects demonstrated accurate time interval perception, whereas the CTL subjects did not. Although the vestibular system is crucial for balance and spatial awareness, the proprioceptive system, in combination with visual and cognitive strategies, as well as motor efference copies, can help individuals with labyrinthine defects in separately perceiving distances and angles. However, this compensatory approach becomes less effective when these tasks are combined. These findings are relevant for space (planetary) exploration because exposure to microgravity mimics loss of vestibular otolith function.